ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMERIKSAAN ANTENATAL CARE KUNJUNGAN PERTAMA PADA IBU HAMIL - Sri Dinengsih; Riani Diana Putri (Jurnal Maternitas Kebidanan, 2023)
ANC visits are contacts between pregnant women and health workers to check their pregnancies and optimize the physical and psychological health of pregnant women. If a pregnant woman does not make an ANC visit, she cannot detect abnormalities in the mother and fetus, she does not know the risks that might occur to the mother, she cannot detect diseases suffered by the mother during pregnancy. Purpose; This study was to analyze the factors related to the first visit antenatal care in the working area of ​​the Karangpawitan Health Center, Garut Regency. Research with a cross sectional approach. The research sample used total sampling, namely all pregnant women in Sindangpalay Village, Working Area of ​​the Karangpawitan Health Center, Garut Regency, as many as 74 respondents in April 2019. The instrument was a questionnaire. Data analysis used the chi-square test. Research results: that there is a relationship between knowledge variables with a p-value of 0.004, education variable with a p-value of 0.002, motivation variable with a p-value of 0.017 and family support variable with a p-value of 0.014 on ANC examination K1. That knowledge, education, motivation and family support have a relationship with ANC K1 examination. It is hoped that it can provide health education about the importance of the first visit ANC examination both at posyandu and in class activities for pregnant women so that pregnant women increase their knowledge.